INTEGRASI LEGENDA BULUSAN SUMBER DALAM PEMBELAJARAN SASTRA TRADISIONAL ANAK UNTUK MENANAMKAN NILAI KEARIFAN LOKAL - Arica Lungdiansari, Nevananda; Suryandari, Nurul; Kanzunnudin, Mohammad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the integration of the Bulusan Sumber legend in traditional children's literature learning as an effort to instill local wisdom values. The study uses a qualitative approach with a descriptive type. Data sources include the text of the Bulusan Sumber legend, story fragments, and supporting literature related to traditional literature and local wisdom. The data collection technique uses a cross-reading technique by noting parts that contain local wisdom values. Data analysis uses the Miles and Huberman model which includes data reduction, data presentation, and drawing conclusions. The results show that the Bulusan Sumber legend contains religious values ​​reflected in the attitudes of the characters who connect life with God, moral values ​​in the form of honesty and responsibility, social values ​​in the form of mutual cooperation and care, and cultural values ​​related to traditions and regional origins. The integration of legends in traditional children's literature learning has the potential to increase student engagement, cultural literacy, and character formation in a contextual and meaningful manner.